IMPACT OF FLOODS ON THE ENVIRONMENT, NATURAL ECOSYSTEM AND DEVELOPMENT STRATEGIES FOR MINIMIZING THIS IMPACT IN IBAJI LGA OF KOGI STATE - Abraham Abiodun Bamisile (World Journal of Biology Pharmacy and Health Sciences, 2026)
This study investigated the impact of Floods on The Environment, Natural Ecosystem and Development Strategies for Minimizing this Impact in Ibaji LGA of Kogi State. The objectives of the study are to identify the impact of floods on the environment and natural ecosystem, identify how floods affect the ecosystem, and state the strategic ways of minimizing the impact of flood in the study area. It is used purposive sampling technique and population of the study are 11,400. The findings of the study revealed that destruction of crops and damage of vital infrastructure and preventing access to essential public services are the major impacts in the study area, and also the major livelihood affected in the study area is agricultural system (farming). The study continues revealing that tackling climate change, forecasting early warning, monitoring, and preparation of contingency plans are the best strategies to minimize the impact of flood in the study area. The study recommends government to promote natural flood management techniques and enhance forecasting and warning system to improve preparedness and response, encourage the adoption of resilient infrastructure designs that can withstand and adapt to flooding, promote community-based initiative for flood preparedness, and as well as to conduct public awareness campaign to educate individuals about the importance of minimizing the impact of floods on the environment and ecosystem.